Occipito-cervical fusion approach to Hangman’s fracture on osteoporosis patient - Glen Sandi Saapang; I Gusti Ketut Agung Surya Kencana; Tjokorda Gde Bagus Mahadewa (Neurologico Spinale Medico Chirurgico, 2022)
An unstable Hangman fracture in an elderly patient is a condition that requires special consideration in selecting a surgical approach. In a healthy sixty-year-old man with a good Karnofsky score, a cervical X-ray and non-contrast CT-scan (NCCT) were performed to confirm the diagnosis. Installation of cervical traction with light weights first followed by occipito-cervical fusion has shown improvement in fracture alignment without complications, even with limited resources. Postoperative radiological examination showed good realignment with lateral mass screw fixation. From this case, it can be seen that the selection of the right surgical procedure in elderly patients is important, especially for those who do not have significant comorbidities.